AK-1, a specific SIRT2 inhibitor, induces cell cycle arrest by downregulating Snail in HCT116 human colon carcinoma cells. Issue 2 (28th January 2015) - Cheon, Min Gyeong; Kim, Wootae; Choi, Minji; Kim, Ja-Eun
Highlights: SIRT2 inhibitor destabilizes Snail and then induces G1 arrest in HCT116 colon cancer cells. The mechanism by which SIRT2 inhibitor destabilizes Snail is possibly dependent on NF-kappaB/CSN2 pathway. SIRT2 inhibitor is a potential therapeutic agent for the treatment of colon cancer. Graphical Abstract: Abstract: SIRT2, a member of the sirtuin family, is involved in the regulation of a variety of physiological functions. In addition, SIRT2 has been studied in the context of pathological conditions including neurodegenerative diseases, metabolic syndrome, and cancer. The effect of SIRT2 on cancer cell growth depends on cancer tissue type. To investigate the role of SIRT2 in colon cancer, we treated HCT116 human colon cancer cells with the SIRT2-specific inhibitor AK-1, a cell-permeable benzylsulfonamide. AK-1 treatment induced proteasomal degradation of the Snail transcription factor through inactivation of the NF-κB/CSN2 pathway. Reduction in the level of Snail resulted in upregulation of p21, a cyclin-dependent kinase inhibitor, leading to G1 arrest, slow proliferation, and slow wound-healing activity. The regulation of Snail–p21 axis by AK-1 also occurs in HT-29 colon cancer cells. Therefore, inhibition of SIRT2 using AK-1 would be a beneficial intervention in the treatment of colon cancer.